2020
DOI: 10.1186/s12904-020-00584-3
|View full text |Cite
|
Sign up to set email alerts
|

Supportive and palliative care indicators tool (SPICT™): content validity, feasibility and pre-test of the Italian version

Abstract: Background: Difficulties in identifying patients at risk of clinical deterioration or death represent one of the main barriers to Palliative Care (PC) development in the community. Currently, no specific Italian tools aimed at identifying patients with PC needs are available. Of the different European tools available, the SPICT™ can be used easily in any kind of setting and does not include the Surprise Question. The purpose of the study was to translate, cross-culturally adapt and pre-test the Italian version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The cultural adaptation process for the instrument showed a semantic equivalence with the SPICT-ES ™ translated into Spanish by Fachado A et al, (2018), making it necessary to add some words/expressions in 3 items to more clearly describe the indicators, similar to what was done in other adaptations [23,24]. Based on the concordance level, it is interpreted that SPICT-ES CH corresponds to an instrument that gathers evidence of content validity, with clear items, coherent with the construct to be measured and feasible to be submitted to the following stages.…”
Section: Discussionmentioning
confidence: 99%
“…The cultural adaptation process for the instrument showed a semantic equivalence with the SPICT-ES ™ translated into Spanish by Fachado A et al, (2018), making it necessary to add some words/expressions in 3 items to more clearly describe the indicators, similar to what was done in other adaptations [23,24]. Based on the concordance level, it is interpreted that SPICT-ES CH corresponds to an instrument that gathers evidence of content validity, with clear items, coherent with the construct to be measured and feasible to be submitted to the following stages.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize common method bias and maximize content validity, the authors used multiple strategies, such as multidimensional scales for each construct; simple language suitable for the target audience; pre-test of the questionnaire and feedback from children, academics and teachers of the target grades’ participants; positive and negative items were used in a balanced way; teachers were involved as intermediaries of the whole process [ 60 , 61 , 62 , 63 , 64 ]. Harman’s single factor test revealed that systematic variance was not a problem in the present study [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“… 17 Furthermore, several tools including general as well as disease-specific indicators have been developed: the Gold Standards Framework Prognostic Indicator Guidance (GSF-PIG), the Supportive and Palliative Care Indicators Tool (SPICT) and the RADPAC indicators. 15 , 18 , 19 However, these tools are rather focused on the terminal phase and have not been validated for COPD.…”
Section: Introductionmentioning
confidence: 99%